Proceedings of the International Conference "Topical Problems of Philology and Didactics: Interdisciplinary Approach in Humanit 2019
DOI: 10.2991/tphd-18.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Approach to Health Lifestyle Model Development in Students

Abstract: The article deals with the interdisciplinary approach to the development of models of healthy lifestyles. The results of the research on the state of health of students, health care motivations. The issues of active lifestyle to develop the value potential of health culture are analyzed. As a vector of health formation, the individual technology is suggested as a certain behavioral strategy whose development requires consolidation of efforts of specialists and critical understanding of information through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…According to the results of the research carried out by a number of specialists, who conducted their studies in the field of digital education [15][16][17][18], as well as their own analysis [19], it can be concluded that the educational environment in the disciplines of Physical Culture and Sports should include a number of components:…”
Section: Results Of the Researchmentioning
confidence: 99%
“…According to the results of the research carried out by a number of specialists, who conducted their studies in the field of digital education [15][16][17][18], as well as their own analysis [19], it can be concluded that the educational environment in the disciplines of Physical Culture and Sports should include a number of components:…”
Section: Results Of the Researchmentioning
confidence: 99%
“…Social status implies that society provides a person with certain opportunities and, for its part, expects from him/her certain achievements that activate the motivation of efficiency. Based on this, the process of promoting health is provided and modulated by the combined action of motivation of an individual and social significance of his/her activities [9].…”
Section: Resultsmentioning
confidence: 99%
“…Convincing evidence of the high importance of health at the normative level declared, can be the fact that, choosing from a corresponding list of statements regarding health, almost half of young Russians chose the option "health is the most important thing in life (Sedova et al 2018;Kramskoy et al 2019); all important decisions must be made so as not to harm health." About the same number of young people has placed their health on the same level of importance as work, study, leisure, entertainment, social life, and only one out of six respondents admitted that they could sacrifice their health for extra income, hobbies, etc.…”
Section: The Health In the Value System Of Russian Youthmentioning
confidence: 99%